Application of Acrostic Techniques to Improve Poetry Writing Ability by UMN Al-Washliyah Students in The Literature Appreciation Course for Elementary Children - Putri Juwita; Desniarti Desniarti; Tiflatul Husna; Nurmarina Nurmarina (Westscience Press, 2023)
The background to this research is the students' lack of understanding of the concept of poetry so that poetry writing tends to be written in the form of stories with paragraphs. These findings show that students' ability to write poetry at school is still low. This research aims to improve the ability of students in the Primary School Teacher Education Study Program Semester 4 V at Al Washliyah Muslim Nusantara University in writing poetry using the acrostic technique. The research was carried out using classroom action procedures (PTK). Data collection techniques use observation and test techniques. This research is Classroom Action Research (PTK) where the assessment is cyclical consisting of 4 stages, namely: (1) planning, (2) implementation, (3) observation and (4) reflection. The sample in the research here is all 4V semester students totaling 39 people. The research results show that the ability of students in the fourth semester of the Teacher Education Study Program in writing poetry in the pretest obtained a score of 60.10 and a completeness level of 16%. In the first cycle they obtained an average score of 64.72 and a completeness level of 49%. In cycle II the average score was 83.90 and the level of learning completeness was 92%. From the results of this analysis, it was concluded that the ability to write poetry using the acrostic technique of students in the fourth semester of the FKIP Elementary School Teacher Education Study Program increased. Based on the criteria for classical learning completeness, this learning has achieved the target of classical learning completeness. In other words, this acrostic technique helps students convey ideas, thoughts and feelings through imagination in the form of poetry.